A systematic review of the epidemiology of pediatric autoimmune encephalitis: disease burden and clinical decision-making - Santoro, Jonathan D.; Demakakos, Panayotes; He, Shiying; Kumar, Swati; Murton, Molly; Tennigkeit, Frank; Hemingway, Cheryl (Frontiers in Neurology, 2024)
Autoimmune encephalitis (AIE) comprises a group of rare, immune system-mediated conditions. Clinical manifestations among children are not well-characterized, and there are challenges in testing and diagnosis. This can result in treatment delays, which has been found to correlate with poorer long-term outcomes. This challenge is exacerbated by the scarcity of epidemiological reporting of AIE. The objective of this systematic literature review (SLR) was to identify studies reporting epidemiological data on AIE in children.MEDLINE, Embase, the Cochrane Library, and the University of York Centre for Reviews and Dissemination (CRD) were searched in May 2023 for studies reporting on the epidemiology of AIE in children. These were supplemented with additional searches of conference proceedings, gray literature, and the reference lists of identified SLRs. Quality of studies were assessed using a modified version of the Joanna Briggs Institute (JBI) Checklist for Prevalence Studies.Forty-three publications reporting on 41 unique studies were included. Nine studies reported incidence estimates of different subtypes of AIE, with only one reporting the incidence of overall AIE in children ≤18 years, estimated at 1.54 per million children per year in the Netherlands. Three studies reported the incidence of pediatric N-methyl-D-aspartate receptor (NMDAR)-AIE (in United Kingdom [UK], Hong Kong and Denmark). The other studies reported incidence data for selected populations.This SLR highlights a paucity of epidemiology data for AIE in children, which is likely reflective of difficulties in testing and diagnosis. There is a clear need for further research and awareness of these challenges in clinical practice to avoid treatment delays and improve patient outcomes. A deeper understanding of the epidemiology of AIE will help determine the worldwide burden of disease and inform research, health policies and clinical decisionmaking.